Tax and Customs Revenues During the Kingdom of Aceh Darussalam - Anwar, Anwar (Riwayat: Educational Journal of History and Humanities, 2024)
The Kingdom of Aceh Darussalam (ruled 1514 to 1903) was a famous Islamic kingdom in the history of the archipelago. The peak of its glory was reached during the time of Sultan Iskandar Muda (reigned 1607-1636). The glory and fame of this kingdom was created because of Sultan Iskandar Muda's ability to regulate political-economic policies, especially the tax and customs sectors as the main pillars of the kingdom's wealth income. This article discusses the income of royal wealth from the tax and customs sector, which includes tax and excise objects, the management of their collection and the sultan's policies in reviving the tax sector. Sultan Iskandar Muda has built the port of Bandar Aceh into a large port and concentrated the trade in pepper and commodities which have a high selling value on the world market only in this city. The impact is that Bandar Aceh is visited by merchant ships from the archipelago and abroad. Traders, foreign and local, are charged taxes and excise, such as adat stamp or adat lapik cap (the sultan's permission to land), adat wase kuala (fees for guarding parking and guarding ships entering and leaving the port), stall tax on merchandise/ trading place. Taxes are also collected from local traders who sell at the market. Apart from that, land tax is also levied (wase tanoh), farmers who receive irrigation are subject to the customary but umong tax, farmers who seek forest products are subject to wase gle tax), people who litigate in court are subject to the customary tuha tax, people who die but do not leaving his heirs his wealth to be put into the royal treasury, as well as foreign traders. Income from various types of taxes and excise is intended to build various facilities and infrastructure to strengthen and advance the kingdom